2022
DOI: 10.3389/fped.2022.914545
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Development of the Hip in Normal Infants Under Six Months of Age by the Graf Ultrasound Method

Abstract: ObjectiveThis large-sample observational study aims to analyze the morphological development of the hip joint in Chinese normal infants under 6 months of age by the Graf ultrasound method.MethodsThe clinical and ultrasound data of infants who underwent early screening for developmental dysplasia of the hip (DDH) in the authors' clinic from January 2011 to December 2019 were analyzed retrospectively. The standard Graf method was used to measure the hip joint α angle, β angle and femoral head coverage (FHC). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(28 reference statements)
0
4
0
Order By: Relevance
“… 42 Studies have shown that most immature hips diagnosed via ultrasonography mature without any interventions during the first weeks of life. 92 However, it must be noted that in 1 of the largest studies reporting late detection rates before and after selective screening implementation in England, 87 the rate remained unchanged compared with prior clinical screening policy. The presented late detection rate (1.3 per 1000 neonates) was also extremely high, as studies with clinical screening only have had much lower rates (eg, a study in Sweden 84 that found a rate of 0.12 per 1000 neonates).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 42 Studies have shown that most immature hips diagnosed via ultrasonography mature without any interventions during the first weeks of life. 92 However, it must be noted that in 1 of the largest studies reporting late detection rates before and after selective screening implementation in England, 87 the rate remained unchanged compared with prior clinical screening policy. The presented late detection rate (1.3 per 1000 neonates) was also extremely high, as studies with clinical screening only have had much lower rates (eg, a study in Sweden 84 that found a rate of 0.12 per 1000 neonates).…”
Section: Discussionmentioning
confidence: 98%
“…Another advantage is that if the selective screening is performed in delayed schedule for patients with hips with clinical suspicion, many of these hips have had time to mature and stabilize . Studies have shown that most immature hips diagnosed via ultrasonography mature without any interventions during the first weeks of life . However, it must be noted that in 1 of the largest studies reporting late detection rates before and after selective screening implementation in England, the rate remained unchanged compared with prior clinical screening policy.…”
Section: Discussionmentioning
confidence: 99%
“…Between the infants with DDH Graf type II, hips with maturational deficit Graf type IIa (-) were the most frequent finding (74% of DDH Graph type II) in our study. Many authors reported that 85% of DDH Grapf IIa (-) reached normality without any treatment at the end of the 3rd month of age (10). A greater number, even 35% of the hips with maturation deficit in our investigation turned into true dysplastic hips throughout the treatment monitoring period.…”
Section: Discussionmentioning
confidence: 42%
“…Bilgili et al determined the cut-off value of 55° on initial sonography as an independent predictor of worsening sonographic findings (9). It has been reported that 85% of Graf type IIa (-) hips have developed into normal hips without any treatment by the age of 3 months and then enter a plateau period during the 4 to 6th month (10).…”
Section: Introductionmentioning
confidence: 99%
“…The hip joint's development is a dynamic process that occurs during the neonatal period and is difficult to assess using direct radiography due to the predominance of cartilage. Hip USG using the Graf classification is the gold standard for detecting DDH in newborns, particularly in the first six months of life [4]. In Türkiye, Graf hip USG screening is a standard method for identifying DDH in newborns and is incorporated into routine newborn evaluations to ensure early detection and treatment of DDH.…”
Section: Introductionmentioning
confidence: 99%